Arylation with Bismuthonium Salts - Maggi, Lorenzo (2021)
Organobismuth reagents have been employed as electrophilic arylating agents since the 1980s, but both their synthesis and use in arylation reactions suffer from poor atom economy. Improvements in the economy of Bi-mediated arylation would render this potentially powerful methodology both general and convenient. This Thesis discusses two approaches towards this goal: arylation catalysed by bismuthonium complexes and synthesis and reactivity of heteroleptic complexes. In particular, the feasibility of a catalytic approach for the arylation of phenols was extensively explored. The investigation separated the overall transformation in three key steps: oxidation, transmetalation and arylation. Direct access to tetraarylbismuthonium salts from readily available triarylbismuth species was provided by a new oxidation- transmetalation sequence. Attempts to merge the arylation step with the previous two proved challenging. Intrinsic incompatibilities of some components of the system were identified. Time separation of the oxidation-transmetalation steps from the arylation phase allowed the overall transformation to be performed in one-pot, however, at the expense of the catalytic approach.